Cost‐Effective Absorber Patterning of Perovskite Solar Cells by Nanosecond Laser Processing. Issue 2 (20th February 2017) - Turan, Bugra; Huuskonen, Arne; Kühn, Irina; Kirchartz, Thomas; Haas, Stefan
Abstract : Perovskite solar cells have shown a tremendous performance increase in the last years with conversion efficiencies >20%. For the successful application of this technology, an interconnection process is required to create large area solar modules, preferably with the help of precision laser processing. By now, only a few groups have started investigations of this topic. Here, we report on methods and ways to characterize and optimize the perovskite absorber removal process (P2), by means of nanosecond pulsed laser ablation with wavelengths of 355, 532, and 1, 064 nm. With short‐pulsed lasers, the underlying ablation mechanisms of the perovskite material differ significantly from other thin‐film photovoltaic technologies, and the characterization with regards to the formation of contact resistances is indispensible. We show that process optimization based on a morphological evaluation is not sufficient to generate interconnections, without severe influence on the solar module performance. Abstract : A procedure for the generation of a high‐efficiency series connection of perovskite solar modules is presented, using cost‐effective nanosecond laser sources for the critical absorber removal process .